Freedom of expression as self-restraint - Kramer, Matthew H., 1959- (Oxford : Oxford University Press, 2021)
This text argues for the absolutist position on the freedom of expression, and how this principle is integral for society. This title also explores some of the most common arguments regarding freedom of expression including pornography and banning advocacy of hateful creeds.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 21, 2021).
Keywords: Freedom of expression; Self-control.